Estudio preliminar de la evolución geomorfológica del abanico aluvial de Lima (Perú) e implicancias en el análisis de amenazas asociadas al cambio climático - Villacorta Chambi, Sandra Paula (2015)
[ENG] Lima, located on the central coast of Peru, is the capital and largest city with a population of more than 9 million inhabitants. Lima is situated over the boundary of two tectonic plates: Nazca and South American plates. A large portion of the city is constructed over the unconsolidated sediments of the Rimac River alluvial fan. These geological and geomorphological features make the area a high risk zone related to devastating earthquakes and tsunamis and the subsequent possible loss of life. Therefore, it is vitally important that the origin and geological dynamics of Lima’s alluvial fan are fully understood to enable and ensure the development of workable risk management plans. In this way, a significant investigation is being conducted to collect and analyse information that can be used to understand how future geo-hydrological events may take place and how these events will be affected by climate changes (deglaciation resulting in isostatic rebound and/or eustatic adjustment) or tectonism. This project is a joint initiative between the Geological, Mining and Metallurgical Institute (INGEMMET, the Peruvian Geological Survey) in partnership with the Geological Survey of Spain (IGME) and the Polytechnic University ofMadrid (UPM) to investigate these phenomena and promote the research on paleo-floods on Peru. This paper presents the initial analysis of available information and the generation of preliminary geomorphological mapping, mainly of fluvial terraces, that allowed elucidation of hypotheses on the evolution of the fan and project future investigations to carry out. Geoforms show that previous rainfalls were bigger than today. The great anthropization of the area (dense road network, urban concentration and sprawl) should explain the flooding processes and flow dynamics.